2020
DOI: 10.1038/s41592-020-0961-2
|View full text |Cite
|
Sign up to set email alerts
|

EthoLoop: automated closed-loop neuroethology in naturalistic environments

Abstract: Accurate tracking and analysis of animal behavior is crucial for modern systems neuroscience. Animals can be easily monitored in confined, well-lit spaces or virtual-reality setups. However, tracking freely moving behavior through naturalistic, three-dimensional (3D) environments remains a major challenge. A closed-loop control that provides behavior-triggered stimuli and thus structures a behavioral task, is also more complicated in free-range settings. Here, we present EthoLoop: a framework for studying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…However, they are hard to combine with neuronal recordings. A smaller number of published complex behavioral environments include wireless recording of neural activity from single freely moving animals, although with limited behavioral control 29, 30 or with a simple behavioral loop that encouraged one specific behavior to obtain a reward 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are hard to combine with neuronal recordings. A smaller number of published complex behavioral environments include wireless recording of neural activity from single freely moving animals, although with limited behavioral control 29, 30 or with a simple behavioral loop that encouraged one specific behavior to obtain a reward 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, they are often hard to combine with neuronal recordings. Only a few behavioral environments include wireless recording of neural activity from single freely moving animals (Finkelstein et al, 2015;Nourizonoz et al, 2020;Yartsev & Ulanovsky, 2013). The novelty of the RIFF in this emerging field lies in its integrated approach allowing a rich repertoire of behavioral tasks combined with wireless electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An attractive feature of deep networks is the high-level of abstraction of the data-driven features that are exploited for classification. There are attempts to use this approach to study behavior in less restricted or controlled settings (Nourizonoz et al, 2020). In summary, with the progress in the field of deep learning, deep artificial neural networks is becoming popular in computational ethology.…”
Section: Social Behavior and Tracking Multiple Animals In The Homecage Using Deep Learningmentioning
confidence: 99%
“…We used events to represent behaviour and event-processing and microservices to achieve 219 online capabilities(Larsen et al, 2021). Several studies have demonstrated the power of online 220 processing in closed loop assays in neuroscience(Grosenick et al, 2015;Nourizonoz et al, 2020), 221 to manipulate pitch in songbirds (Lohr et al, 2003; Brumm and Slabbekoorn, 2005; Riedner and 222 Adam, 2020) or to provide virtual reality (Ahrens et al, 2012; Reiser and Dickinson, 2008; Harvey 223 et al, 2009). Those studies take advantage of computationally attractive features, such as action 224…”
mentioning
confidence: 99%